Rancang Bangun Sistem Pemesanan Katering Digital Berbasis Web di Santosa Catering - Anggraeni, Dwi Puspita (Universitas Gajah Putih, 2022)
The rapid development of information technology enables small and medium-sized enterprises, such as catering businesses, to improve service efficiency through digitization. Santosa Catering faces several obstacles in the operational process, including an imbalance between ordering capacity and delivery capability as well as a lack of customer access to menu and pricing information. This research aims to design and implement a web-based digital catering ordering system at Santosa Catering as a solution to these problems. Using the Waterfall development method, this system is designed to facilitate the management of menu data, orders, and reports in real-time. The results show that the system is able to improve operational efficiency through automation of recording and presentation of menu information that is more accessible to customers. System testing using the Black Box Testing method ensures that each feature functions optimally, including the management of ordering capacity, report generation, and package menu preparation. This web-based ordering system is expected to be an effective platform for Santosa Catering in providing better services and supporting business growth.